2013
DOI: 10.1128/mbio.00597-12
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1 Is Required for Resistance to Coccidioidomycosis in Mice

Abstract: We assessed the role of Dectin-1 in the immune response to the pathogenic fungus Coccidioides, both in vitro and in vivo, using mice with a targeted mutation in Clec7a. Elicited peritoneal macrophages responded to formalin-killed spherules (FKS) and alkali-treated FKS by secreting proinflammatory cytokines in a Dectin-1- and β-glucan-dependent manner. The responses of bone marrow-derived dendritic cells (BMDC) to the same stimulants were more complex; interleukin 1β (IL-1β) and tumor necrosis factor alpha (TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 73 publications
(71 reference statements)
2
71
0
2
Order By: Relevance
“…In a set of BXD recombinant inbred mice, we found an association between the expression of full-length Dectin-1 and resistance to coccidioidomycosis (20). Expression of Dectin-1 on macrophages is regulated by a number of cytokines, and we found that genetically resistant DBA/2 mice express much more Dectin-1 in their infected lungs than do two genetically susceptible mouse strains (23). However, even this reduced level of Dectin-1 expression is somewhat protective, because Dectin-1 knockout (KO) mice are even more susceptible than B6 mice.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In a set of BXD recombinant inbred mice, we found an association between the expression of full-length Dectin-1 and resistance to coccidioidomycosis (20). Expression of Dectin-1 on macrophages is regulated by a number of cytokines, and we found that genetically resistant DBA/2 mice express much more Dectin-1 in their infected lungs than do two genetically susceptible mouse strains (23). However, even this reduced level of Dectin-1 expression is somewhat protective, because Dectin-1 knockout (KO) mice are even more susceptible than B6 mice.…”
mentioning
confidence: 82%
“…There is experimental evidence in mice that CLR are important for resistance to opportunistic fungal pathogens, such as Candida albicans and Pneumocystis carinii (30,31). We recently showed that Dectin-1 is required for resistance to Coccidioides immitis in mice, and so far this is the only example of Dectin-1 playing a role in resistance to a primary pathogenic fungus (23). A mutation in human Clec7A that deletes the carbohydrate recognition domain on Dectin-1 predisposes to a mild form of vulvovaginal candidiasis and to onychomycosis, demonstrating that the gene plays a nonredundant role in resistance to mucocutaneous fungal infections in humans (32).…”
mentioning
confidence: 99%
“…The mannose receptor and Mincle are dispensable for resistance to pulmonary coccidioidomycosis (18,47). All three Dectin receptors contribute to recognition of spherules (18,47,48; unpublished data). However, these receptors may function either alone or in synergy in resistance to pulmonary and subcutaneous infections and their regulatory mechanisms await clarification (18,43).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, increased IL-10 production results in increased susceptibility, and conversely, IL-10 KO mice are more resistant than the susceptible parental strain, closely resembling DBA/2, the most resistant inbred strain [60]. The only known driver of those differences in mice is Dectin-1, the β glucan receptor, which is expressed on dendritic and other myeloid cells [61]. There is a difference in the structure and function of Dectin-1 in susceptible B6 mice and resistant DBA/2 mice that is based on alternative splicing of the encoding gene, Clec7a [59].…”
Section: Immunologymentioning
confidence: 99%